2016
DOI: 10.1007/s12264-016-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine Prevents Adaptation of the Hippocampal Glutamate System in Chronic Morphine-Treated Rats

Abstract: Chronic exposure to opioids induces adaptation of glutamate neurotransmission, which plays a crucial role in addiction. Our previous studies revealed that agmatine attenuates opioid addiction and prevents the adaptation of glutamate neurotransmission in the nucleus accumbens of chronic morphine-treated rats. The hippocampus is important for drug addiction; however, whether adaptation of glutamate neurotransmission is modulated by agmatine in the hippocampus remains unknown. Here, we found that continuous pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In the nucleus accumbens, repeated agmatine exposure reduces increases in extracellular glutamate levels through reversing the increase in release but not uptake after naloxone‐precipitated withdrawal and abolishes the up‐regulation of the expression of the GLuN1 subunit of NMDA receptors in repeated morphine‐treated rats (Wang et al, 2011). In the hippocampus, both acute and repeated agmatine administration reduces elevated extracellular glutamate levels by decreasing release and increasing the uptake after naloxone‐precipitated withdrawal and inhibits the reduction in the level of the GluN2B subunit, but not the GLuN1 subunit, of NMDA receptors in chronic morphine‐treated rats (Wang et al, 2016). Moreover, considering that chronic exposure to opioids impairs adult hippocampal neurogenesis, particularly at the progenitor stage, in the hippocampal dentate gyrus (Bayer et al, 2015; Kahn et al, 2005; Zheng et al, 2013), agmatine abolishes the chronic morphine‐induced decrease in proliferation of hippocampal progenitors in vivo and in vitro , possibly due to an increase in cAMP‐CREB‐BDNF signalling (Liu et al, 2018).…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
“…In the nucleus accumbens, repeated agmatine exposure reduces increases in extracellular glutamate levels through reversing the increase in release but not uptake after naloxone‐precipitated withdrawal and abolishes the up‐regulation of the expression of the GLuN1 subunit of NMDA receptors in repeated morphine‐treated rats (Wang et al, 2011). In the hippocampus, both acute and repeated agmatine administration reduces elevated extracellular glutamate levels by decreasing release and increasing the uptake after naloxone‐precipitated withdrawal and inhibits the reduction in the level of the GluN2B subunit, but not the GLuN1 subunit, of NMDA receptors in chronic morphine‐treated rats (Wang et al, 2016). Moreover, considering that chronic exposure to opioids impairs adult hippocampal neurogenesis, particularly at the progenitor stage, in the hippocampal dentate gyrus (Bayer et al, 2015; Kahn et al, 2005; Zheng et al, 2013), agmatine abolishes the chronic morphine‐induced decrease in proliferation of hippocampal progenitors in vivo and in vitro , possibly due to an increase in cAMP‐CREB‐BDNF signalling (Liu et al, 2018).…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
“…Glutamate system in the brain contributes to the adaptive alterations induced by chronic drug exposure [24,26]. Actions of glutamate are mediated through its receptors, among which the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs), the N-methyl-D-aspartate receptors (NMDARs), and the metabotropic glutamate receptors (mGluRs) are the major glutamate receptors that are involved in drug addiction [24,27,28].…”
Section: Glutamate Systemmentioning
confidence: 99%
“…In addition, cystine/glutamate antiporter (xCT) is co-localized with GLT-1 in astrocytes to modulate glutamate homeostasis. Studies showed that chronic exposure to morphine reduced glutamate uptake, and this effect was associated with downregulation of glutamate transporters, mainly GLT-1 ( Dunbar and Pulai, 1998 , Mao et al, 2002 , Marek et al, 1991 , Ozawa et al, 2001 , Wang et al, 2016 ). Furthermore, recent study from our lab showed that chronic exposure to hydrocodone reduced the expression of GLT-1 and xCT in the nucleus accumbens (NAc) ( Wong and Sari, 2023 ).…”
Section: Introductionmentioning
confidence: 99%